Sinus Headache, Migraine, and the Otolaryngologist : A Comprehensive Clinical Guide - Mehle, Mark E. (Springer International Publishing : Imprint: Springer, 2017)
This volume serves as a comprehensive and useful guide for ENT and allergy physicians in the recognition, diagnosis, and treatment of patients who suffer from sinus headaches and migraines. The text reviews key issues such as identification and management of migraine, and appropriate surgical and nonsurgical treatment that is often not part of ENT or allergy resident training. With 20% of women and 6% of men having migraines (only 50% recognized) this text also serves to expand management options to physicians already medically or surgically treating sinuses or seeing cosmetic patients with head and neck concerns. Other forms of intervention in migraineurs, such as surgery, Botulinum Toxin injections and adjunctive and integrative therapy, are covered. Sinus Headache, Migraine, and the Otolaryngologist will be an invaluable resource for ENT and allergy specialists, and any physician or medical professional with an interest in sinus headache or migraine.